Extensive gene tree discordance and hemiplasy shaped the genomes of North American columnar cacti - Copetti, Dario; Búrquez, Alberto; Bustamante, Enriquena; Charboneau, Joseph L. M.; Childs, Kevin L.; Eguiarte, Luis E.; Lee, Seunghee; Liu, Tiffany L.; McMahon, Michelle M.; Whiteman, Noah K.; Wing, Rod A.; Wojciechowski, Martin F.; et al. (National Academy of Sciences, 2017)
Convergent and parallel evolution (homoplasy) is widespread in the tree of life and can obscure evidence about phylogenetic relationships. Homoplasy can be elevated in genomes because individual loci may have independent evolutionary histories different from the species history. We sequenced the genomes of five cacti, including the iconic saguaro of the Sonoran Desert and three other columnar cacti, to investigate whether previously uncharacterized features of genome evolution might explain long-standing challenges to understanding cactus phylogeny. We found that 60% of the amino acid sites in proteins exhibiting homoplasy do so because of conflicts between gene genealogies and species histories. This phenomenon, termed hemiplasy, is likely a consequence of the unusually long generation time of these cacti.